Use Isotopes to Identity the Origin of Surface Water and Groundwater in ameriyat AL-Fallujah, Center Iraq - AL-Dulaimi, Ali M.; Al- Shamma’a, Ayser M. (Iraqi Journal of Science, 2018)
Isotope tracer methods were used to determine flow paths, recharge areas, and relative age for groundwater in the Ameriyat Al- Falluja Al-Anbar governorate. The isotope of surface water and groundwater in the Ameriyat Al- Falluja area was assessed using a stable isotope technique. Data stable isotope parameters (2H and 18O) for three surface water and five groundwater samples were detected. The comparison of hydrogen and oxygen isotope compositions between groundwater and Euphrates River water demonstrated that the composition of the hydrogen and oxygen isotopes from Euphrates River matched that of the local meteoric water. This indicated that rainfall is the primary source of the river water. Environmental Isotopes results show that the surface water and groundwater originates from direct leakage through permeable beds. There is an interaction between Euphrates and groundwater wells in the study area except in the W1 and W5 wells sites.